Economic Security of the Region’s Transport Complex - Papp Vasyl V.; Boshota Nelja V. (Bìznes Inform, 2020)
The article substantiates the urgency of the development of the transport sector of the region as an important component of improving the economic security of the country, outlines the importance of the transport sector in ensuring the effective functioning of the economic system of the country. Improving the economic security of the transport sector is the basis for guaranteeing the security of regions, countries, a condition for sustainable socio-economic development. The relevance of the research topic is due to the role of the transport sector in the regional economy, as well as the unstable financial situation in the industry and the national economy as a whole. The purpose of the article is to study the organizational aspects of economic security of transport in the region. The article analyzes the main trends in the development of the transport sector, as well as the problems that exist in the industry. The modern features of the development of the system of economic security of the transport sphere of the regions are studied and the place and significance of the transport systems in the regional economy are determined. Indicators of increasing the economic security of the regional transport complex are proposed, possible risks of development and functioning of the transport sphere of the regions are outlined. The main factors that ensure the integrated effect of the functioning of transport infrastructure in the region and its impact on economic security have been identified. Conceptual provisions and institutional preconditions of increase of economic security of the transport complex, and criteria of their interaction with other spheres of economy of region are substantiated. The modern problems of economic security management of the transport complex of the region in connection with ensuring the economic security of the country are considered. The directions of strategic planning of development of the regional transport complex and increase of its economic stability are proposed.